2015
DOI: 10.1007/s10518-015-9859-2
|View full text |Cite
|
Sign up to set email alerts
|

Centrifuge modeling of batter pile foundations under sinusoidal dynamic excitation

Abstract: International audienceBatter pile (or inclined pile) foundations are widely used in civil engineering structures. However, their behavior under dynamic loadings is not yet thoroughly understood. This paper presents an experimental work on the behavior of batter and vertical piles considering dynamic soil-pile-superstructure interactions. A series of dynamic centrifuge tests were performed using sinusoidal excitations. The influence of the base shaking (frequency content and amplitude) and of the height of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 31 publications
(43 reference statements)
8
17
0
Order By: Relevance
“…This paper extends the work of Li et al [42] to more general real earthquake loading and the results confirm the conclusions that batter piles are likely to have beneficial performance. In addition, these beneficial effects are more often observed for batter piles with a short superstructure.…”
Section: Discussionsupporting
confidence: 86%
“…This paper extends the work of Li et al [42] to more general real earthquake loading and the results confirm the conclusions that batter piles are likely to have beneficial performance. In addition, these beneficial effects are more often observed for batter piles with a short superstructure.…”
Section: Discussionsupporting
confidence: 86%
“…Escoffier et al performed centrifuge tests on inclined and vertical pile groups using static cyclic loadings and confirmed the higher horizontal stiffness provided by the inclined pile group. This was also observed by Li and Li et al from dynamic sinusoidal and seismic centrifuge test results. The authors stated that in certain cases, batter piles play a beneficial role on the seismic behavior of the pile foundation system and that their performance depends not only on the characteristics of the earthquakes (frequency content and amplitude) but also on the type of superstructures they support.…”
Section: Introductionsupporting
confidence: 84%
“…which provides an associative flow rule at failure. In practice, although the failure locus defined by Equation 12 represents an attractor for the evolution Equation 11, the flow rule Equation 16 with f ≡ F does not guarantee that, for complex loading conditions, the loading path will never cross the failure surface, reaching states with F > 0 (or Y > 1). Therefore, to prevent the loading path to reach impossible states, the flow direction vector m in the close vicinity of the failure surface is defined by…”
Section: Definition Of Vector Nmentioning
confidence: 99%
“…The models were spun in the centrifuge to increase the g-level in them so that stresses in their ground were equal to those in the prototype. It is also an advantage for the theoretical verification and numerical analysis techniques as the boundary and stress conditions of the ground, which are imposed in the centrifuge model test, have been studied a lot [10][11][12][13]. The tests were carried out at the Korea Advanced Institute of Science and Technology (KAIST) Geo-centrifuge Testing Center using an experimental machine with a 5 m radius and 240 g-ton maximum operating capacity [20][21][22].…”
Section: Dynamic Centrifuge Model Testingmentioning
confidence: 99%
“…The test results showed that the batter piles were significantly affected by the frequency characteristics of the input wave. Li et al [12] conducted dynamic centrifuge model tests to evaluate the behavior of vertical and batter piles. They analyzed the characteristics of the batter piles corresponding to their natural frequency and size of structures.…”
Section: Introductionmentioning
confidence: 99%